Online geocode in postal address using GPS with synchronous database accessing - Mohammad Riyadh R. Sharba; Hakim Adil Kadhim; Salam A. W. Al-Abassi; Nabeel Salih Ali (Institute of Advanced Engineering and Science, 2020)
Postal addressing information is a crucial issue in any organization for business targets, especially in developed countries. Thus, required to convert postal address data to an absolute value like latitude and longitude coordinates by a procedure called geocoding. In this paper, discuss how to make long coordinates into simple geocode via maps services. Besides, conduct a smartphone application to save the geocode with details information to be a GIS for the future used by end-users. The information includes address name, type, and phone number as well as a small note. The app can search for a particular location like hospitals, schools, restaurants, etc.